ANALISIS KINERJA PRODUK UKM BATIK BANYUMAS DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN POTENTIAL GAIN OF CUSTOMER VALUE’S (PGCV) INDEX - Weni Novandari; Sri Murni Setyawati; Siti Zulaikha Wulandari (Jurnal Bisnis dan Ekonomi, 2011)
This study was aimed to determine the product performance of SME products Banyumas batik and identify SME Banyumas Batik’s approach in order to improve their product’s quality based on consumers’ sight. The analysis tools used in this research are Importance Performance Analysis which is used to measure product attribute’s expectations and performance from the consumer point of view and also PGCV Index (Potential Gain of Customer Value's Index) which is used to determine the priority scale of Banyumas batik performance improvements. The results showed that 1) Batik Banyumas’s performance is good from consumer’s perception,shown by the average level value of compatibility between consumer expectations and product performance of 99.32%, that means 99.32% product performance already fulfill consumers’ expectation. 2) There are six indicators of product quality that already meets consumer’s expectations which are product’s quality price level, the diversity of colors, color quality, the diversity of designs / patterns, unique designs / motifs and quality raw material. 3) There are 5 indicators of product quality that need to be improved in Banyumas batik’s quality based on priority scale which are ,fineness of batik, the completeness of product packaging information (brand, manufacturer address, batik name, way of maintenance, etc.), packaging design, color and brand of product packaging.Key words: SME batik product performance, importance performance analysis, PGCV Index (potential gain of customer value's index)